(untitled) (The Review of Diabetic Studies, 2025)
Background: Focal liver lesions (FLLs) constitute one of the significant diagnostic conundrums in the realm of medical practice. Comprehensive approaches, as offered by the gamut of multi-parametric imaging using magnetic resonance imaging techniques such as the incorporation of diffusion-weighted imaging, diffusion tensor imaging, and magnetic resonance elastography, compare favorably with contrast-enhanced ultrasound approaches. This review collates the evidence regarding the differentiation of benign from malignant FLLs using the aforementioned diagnostic modalities. Objective: Evaluate the performance of multi parametric MRI modalities with contrast-enhanced ultrasound methods regarding their ability to identify focal liver lesions, with special reference to sensitivity and specificity .Methods: Data from recent comparative studies evaluating MRE, DWI, DTI, and parametric contrast-enhanced ultrasound were analyzed. Comparisons between diagnostic accuracy metrics such as sensitivity and specificity, ADC and FA values, and stiffness measurements across all modalities were performed. Results: MRE thus showed a sensitivity of 93.8-97.3% and a specificity of 89.9-90.9%, whereas the sensitivity of DWI alone ranged between 77.9-87.6%, while its specificity ranged from 51.5-83.4%. DTI likewise demonstrated significant differences in both ADC values-benign, 2.152 × 10⁻³ mm²/s vs. malignant, 1.212 × 10⁻³ mm²/s (p<0.001)-and FA values-benign, 0.211 vs. malignant, 0.381 (p<0.001). Parametric CEUS resulted in an accuracy of 95.2-95.9%, with excellent inter observer agreement demonstrated with κ=0.99. Conclusion: Multi parametric MRI, particularly the association of MRE and DWI/DTI, shows increased diagnostic accuracy in the differentiation of various FLLs. Though the diagnostic outcome of contrast-enhanced ultrasound with the help of parametric imaging is satisfactory, MRI-based methods show better sensitivity levels, allowing the avoidance of false negative rates. The association of multiple functional parameters enhances the diagnostic confidence.